Experimental evaluation of inactivated and live attenuated vaccines against Mycoplasma mycoides subsp. Mycoides - Mwirigi, M.; Nkando, I.; Aye, R.; Soi, R.; Ochanda, H.; Berberov, E.; Potter, A.; Gerdts, V.; Pérez Casal, J.; Naessens, Jan; Wesonga, H.O. (Elsevier, 2016)
The current control method for contagious bovine pleuropneumonia (CBPP) in Africa is vaccination with a live, attenuated strain of Mycoplasma mycoides subsp. mycoides(Mmm). However, this method is not very efficient and often causes serious adverse reactions. Several studies have attempted to induce protection using inactivated mycoplasma, but with widely contradictory results. Therefore, we compared the protective capacity of the live T1/44 vaccine with two inactivated preparations of Mmmstrain Afadé, inoculated with an adjuvant. Protection was measured after a challenge with Afadé. The protection levels were 31%, 80.8% and 74.1% for the formalin-inactivated, heat-inactivated and live attenuated preparations, respectively. These findings indicate that low doses of heat-inactivated Mmm can offer protection to a level similar to the current live attenuated (T1/44) vaccine formulation.